The effect of consuming banana blossom (musa paradisiaca) on breast milk production in postpartum mothers - Gina Kusuma Nigrum; Ummi Kulsum; Fania Nurul Khoirunnisa (Science Midwifery, 2026)
Background: Breast milk (ASI) contains essential nutrients needed for infant growth, immunity, disease prevention, and cognitive development. Banana flower is known to contain lactagogum compounds that stimulate the hormones oxytocin and prolactin, which can help increase and facilitate breast milk production. Objective: This study aimed to determine the effect of banana flower consumption on breast milk production in postpartum mothers at PMB Krasak Bangsri Jepara. Method: This study used a quasi-experimental design with a one-group pretest-posttest approach without a control group. The sample consisted of 30 postpartum mothers selected using a total sampling technique. Data were collected through questionnaires and observations. The research instruments included a breast milk production questionnaire and a standard operating procedure (SOP) for administering banana flower. Validity testing showed all questionnaire items were valid with r-count values ​​greater than r-table (0.514), while reliability testing using Cronbach's Alpha obtained a value of 0.906, indicating high reliability. Data were analyzed using the Paired Sample t-Test. Result: Statistical analysis showed a p-value of 0.000 (p<0.05), indicating a significant effect of banana flower consumption on breast milk production in postpartum mothers. Conclusion: Banana flower consumption has a significant positive effect on breast milk production in postpartum mothers at PMB Krasak Bangsri Jepara.